PERFORMANCE EVALUATION OF REFLECTORS AND COOLING SYSTEM ON PHOTOVOLTAIC SYSTEM IN KANO NORTHWEST NIGERIA - Tukur, I. A.; Abdullahi, A.; Alhassan, Y.; Abdullahi, B.; Aliyu, A. A.; Tsoho, A. U.; Sani, U. A. (FUDMA JOURNAL OF SCIENCES, 2023)
In the effort to improve the efficiency of a photovoltaic system, previous studies have demonstrated the potential of solar reflectors and cooling systems to enhance the performance of Photovoltaic (PV) systems. However, Result varies from Location to Location and a limited research exists on their combined effect. This study investigates the impact of reflectors and cooling on PV system performance in Kano State, Nigeria. Three Experimental setup were tested; (a solar panel without any modifications (PWM), a solar panel with reflectors sides (PWR), and a solar panel with reflectors and a cooling system (PWRC)). These Experiment were set at the optimum tilt angle of 12o in Kano State, Nigeria. The results show that panel with reflectors and panel with reflectors and cooling system both increased the amount of solar radiation (SR) received by an average of 71.06% compared to the control panel system. The surface temperature (ST) of the PWR and PWRC increased by an average of 46.25% and 28.08%, respectively, compared to the PWM. The PWR and PWRC systems increased the amount of short-circuit current (ISC) produced in the panels with an average of 50.02% and 50.03%. The open-circuit voltage (VOC) drop of the panel in the PWR and PWRC systems decreased by an average of 9.91% and 4.39%, respectively, compare to the PWM system. The power output (PO) of the PWR and PWRC systems also increased by an average of 34.89% and 42.29%, respectively, compare to the PWM system.
Keywords: Photovoltaic system; Cooling system; Panel; Solar radiation; Power output